S3.2 Challenging clinical cases. (20th September 2022) - Singhal, Tanu; Gopalakrishnan, Ram; Soman, Rajeev N.; Patel, Atul
Abstract: S3.2 Challenging clinical cases, September 21, 2022, 4:45 PM - 6:15 PM A case of hepato-splenic-renal candidiasis will be discussed with the aim to track down the causative organism and its likely susceptibility. The role of BDG, selection of the antifungal agent, and duration of therapy will be discussed. A case of an HIV-infected patient with cryptococcal meningitis, pulmonary infection, and pulmonary IRIS will be discussed. A case of Candida auris fungemia and organ infection in a liver transplant recipient who developed serially increasing MIC will be presented. The relevance of MIC, tentative breakpoints, and selection of antifungal agents based on PK PD considerations will be discussed. Talamycosis is usually seen in HIV-infected individuals from North East India. Here we discuss a 3-year-old girl with acute lymphoblastic leukemia from Western India who developed cavitary pneumonia and multiple brain abscesses due to talaromyces. The case posed significant management challenges pertaining to both the fungal infection and cancer. Renal mucormycosis in healthy immunocompetent hosts is an entity generally reported only from India and China. We discuss the case of a previously healthy 3-month-old infant who presented with acute renal failure and renal mucormycosis. The case is unique with respect to the source of infection and management strategy. Treatment of fungal infections involving the draining system of the kidney is challenging mainly due to limited antifungal drug penetration at the site of infection. Challenges in the treatment of amphotericin-resistant Aspergillus terreus pelvicalyceal infections will be discussed. CAPA is a well-known complication of coronavirus disease 2019 (COVID-19), but usually involves the lung alone and rarely disseminates when treated. This case illustrates a rare complication of COVID-19, namely endocarditis caused by Aspergillus . Rhinosporidiosis is a well-known disease that usually involves mucosal surfaces in the head and neck. This case illustrates a rare occurrence, namely dissemination to multiple areas and mimicking the clinical presentation of other cutaneous mycoses.